2018
DOI: 10.3389/fevo.2018.00167
|View full text |Cite
|
Sign up to set email alerts
|

Movement Patterns of African Elephants (Loxodonta africana) in a Semi-arid Savanna Suggest That They Have Information on the Location of Dispersed Water Sources

Abstract: Water is a scarce resource in semi-arid savannas where over half of the African elephants (Loxodonta africana) populations occur and may therefore influence their movement pattern. A random search is expected for an animal with no information on the location of the target resource, else, a direction-oriented walk is expected. We hypothesized that elephants movement patterns show a stronger directional orientation toward water sources in the dry season compared to the wet season. We investigated the movement pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 59 publications
2
25
0
Order By: Relevance
“…Previous studies have shown that elephants are able to memorize the locations of waterholes and navigate back to them without searching (Polansky et al, 2015;Presotto et al 2019;Wato et al, 2018). Here, we show, implicitly, that they integrate memorized spatial information with expected travel time, likely adjusting speed of travel, to arrive at waterholes near nightfall.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Previous studies have shown that elephants are able to memorize the locations of waterholes and navigate back to them without searching (Polansky et al, 2015;Presotto et al 2019;Wato et al, 2018). Here, we show, implicitly, that they integrate memorized spatial information with expected travel time, likely adjusting speed of travel, to arrive at waterholes near nightfall.…”
Section: Discussionsupporting
confidence: 50%
“…Foraging trips between visits to distant water sources during dry season are well documented in elephants (Chamaillé-Jammes et al, 2013;Polansky et al 2015;Shannon et al 2009;Thaker et al 2019;Wato et al 2018). Their thermal physiology also is well understood.…”
mentioning
confidence: 99%
“…Understanding factors that influence spatial heterogeneity in megaherbivore distribution and effects on vegetation has been an important goal for ecologists. However, many studies have either focused on large‐scale patterns across large altitudinal gradients, different vegetation zones, and different rainfall regimes (Bell, 1982; Bohrer, Beck, Ngene, Skidmore, & Douglas‐Hamilton, 2014; Fritz & Duncan, 1994; Holdo, 2003; Howes, Doughty, & Thompson, 2019; Mysterud, Langvatn, Yoccoz, & Nils Chr, 2001; Ngene, Skidmore, Van Gils, Douglas‐Hamilton, & Omondi, 2009), or patterns associated with proximity to focal points such as surface water sources (Chamaillé‐Jammes, Mtare, Makuwe, & Fritz, 2013a; Ndlovu et al., 2018; Wato et al., 2018), human settlements (Neupane, Kwon, Risch, Williams, & Johnson, 2019), and roads (Gaynor et al., 2018), but see (Bond & Loffell, 2001; Coetsee & Wigley, 2016). Consequently, we know little about how fine‐scale habitat patch characteristics such as local variation in topography and edaphic‐driven contrasts in vegetation structure and resource densities may influence megaherbivore effects on vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonality creates pulses in forage quality and availability (Duncan, Reid, Thoss, & Elston, 2005; Egea et al., 2019) and affects distribution of surface water as well as the physiological urge to drink (Chamaillé‐Jammes, Mtare, Makuwe, & Fritz, 2013b; Wato et al., 2018). Generally, there are more forage resources and greater availability of water during the wet season than during the dry season.…”
Section: Introductionmentioning
confidence: 99%
“…Elephants are also heavily water dependent, and make periodic visits to water to hydrate, as well as to use evaporative cooling to thermoregulate (Dunkin et al, 2013;Valls-Fox, 2015). Thus, at the landscape scale, environmental temperature and the distribution of accessible water are expected to be important drivers of elephant movement strategies (Purdon and van Aarde, 2017;Wato et al, 2018). Yet, there has been little work to understand the role of thermoregulation on the dynamic landscape-scale movement decisions of elephants (Dunkin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%